Kecerdasan Buatan dan Rantai Pasokan Manajemen Berkelanjutan: Mengurangi Limbah dan Meningkatkan Efisiensi - Rini Marlina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Artificial intelligence (AI) has emerged as a driving force in the transformation of sustainable supply chain management, aimed at reducing waste and enhancing operational efficiency. In the context of globalisation and rapid technological advancement, companies are required to focus not only on profit but also on the social and environmental impacts of their business activities. This research aims to explore how AI can be applied to enhance sustainability within the supply chain by minimising waste and improving efficiency. Through big data analysis, AI can provide more accurate predictions regarding product demand, enabling companies to optimise production and reduce surplus. This study also identifies the challenges faced by companies in integrating this new technology, including a lack of understanding and skills among workers. By providing insights into best practices and policy recommendations, this research seeks to assist companies in adopting AI as part of their sustainability strategies. The findings indicate that the implementation of AI can not only enhance operational efficiency by up to 30% but also contribute to the reduction of carbon footprints and the achievement of sustainable development goals.